Airline choice and tourism growth in the Azores. (June 2019) - Vieira, José; Câmara, Gualter; Silva, Francisco; Santos, Carlos
Abstract: This study examines the effect of airline choice on tourism growth in the Azores. The results reveal that tourism numbers increased sharply as more alternative choices emerged to visitors after the entrance of low-cost carriers due to airline liberalization. Moreover, different airline types attract different kinds of visitors, contributing to tourism diversification. In particular, low-cost airline tourists are younger than those who travel in full-service airlines or charter flights. They are also more likely to buy a last-minute ticket and to come from Iberian and French markets. Charter flights, however, are important choices for those traveling to the Azores from more distant markets such as Sweden and Denmark. Highlights: Younger travelers are more likely to choose low-cost airlines. Airline liberalization expands tourism. Low-cost airline customers are more likely to buy a last-minute ticket. Airline choice diversification leads to visitors' profile diversification.